Strategic Integration of General and Religious Education in Indonesian Pesantren: Building Holistic Character for National Resilience - Sofwan Manaf; Much. Hasan Darojat; Miftah Hur Rahman Zh; Zahid Zufar At Thaariq; Aldo Redho Syam; Hasim Abdul Jamil (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2025)
This research investigates the strategies employed by pesantren (Islamic boarding schools) to integrate general and religious education, thereby strengthening their role as a pillar of national education. The objective of this study is to identify effective integration models that do not compromise religious identity. The methodology utilised is a multiple case study with a qualitative approach. Data were collected through in-depth interviews, participant observation, and document analysis across several pesantren, and the data were thematically analysed. The research findings reveal that the success of this integration hinges on a holistic approach. A unified curriculum that establishes Islamic values as the foundation for all subjects is key, supported by visionary Leadership and the utilisation of Information and Communication Technology (ICT). Strategic collaboration with higher education institutions proved mutually enriching for the intellectual repository. Primary challenges include the digital divide, budgetary constraints, and remote locations, which are addressed through active curriculum negotiation and innovative management. This integration strengthens the character formation of santri (students) by internalising values such as discipline, empathy, and religious moderation across all aspects of pesantren life. In conclusion, the pesantren offers an excellent educational model that synthesises modernity with local religious wisdom. These findings highlight the need for inclusive supporting policies and further research to examine the long-term impact of this integration on pesantren graduates in the workforce and society